Beyond Vision: Potential Role of AI-enabled Ocular Scans in the Prediction of Aging and Systemic Disorders: Role of AI-enabled Ocular Scans in the Prediction of Aging and Systemic Disorders - Omar, Moaz Osama; Abad Ali , Muhammed Jabran; Qabillie , Soliman Elias; Haji, Ahmed Ibrahim; Takriti , Mohammed Bilal Takriti; Atif, Ahmed Hesham; Rangraze, Imran (Siriraj Medical Journal, 2024)
In all medical subfields, including ophthalmology, the development of artificial intelligence (AI), particularly cutting-edge deep learning frameworks, has sparked a quiet revolution. The eyes and the rest of the body are anatomically related because of the unique microvascular and neuronal structures they possess. Therefore, ocular image-based AI technology may be a helpful substitute or extra screening method for systemic disorders, particularly in areas with limited resources. This paper provides an overview of existing AI applications for the prediction of systemic diseases from multimodal ocular pictures, including retinal diseases, neurological diseases, anemia, chronic kidney disease, autoimmune diseases, sleep disorders, cardiovascular diseases, and various others. It also covers the process of aging and its predictive biomarkers obtained from AI-based retinal scans. Finally, we also go through these applications existing problems and potential future paths.